Vertical Gaze Palsy with Skew Deviation - Pokharel, BR; Thapa, LJ; Paudel, R; Rana, PVS (Kathmandu University Medical Journal, 2015)
With the advancement of neuroradiology, clinical localization followed by radiology, had made neurology more interesting. Vertical gage palsy as presentation cerebrovascular disease is not so common. Vertical gaze palsy usually localizes the lesion to dorsal mid brain. A 56 years male patient presented with sudden onset vertigo, diplopia, transient loss of consciousness and sways toward right side while walking. Clinical examination showed vertical gaze palsy with skew deviation along with swaying towards rt. during walk. MRI brain showed – infarct involving dorsal midbrain at superior colliculus level and medial thalamusKathmandu Univ Med J 2013; 11(4): 342-343